CHILD-FRIENDLY MOSQUES: UNDERSTANDING HADITHS ON TREATING CHILDREN IN THE MOSQUE - Kudhori, Muhammad; Amaliah, Rizky (Nabawi: Journal of Hadith Studies, 2025)
This research examines the hadiths regarding the participation of children who have not yet reached the age of discernment (tamyīz) in mosques and how the Prophet Muhammad (PBUH) addressed situations where they passed in front of people praying. The study stems from the societal debates surrounding the presence of young children in mosques, which can sometimes lead to disturbances or children passing in front of those praying. This research is a qualitative study using the thematic hadith study method by collecting, analyzing, and interpreting hadiths related to the discussed theme. The findings reveal that there are numerous authentic (sahih) hadiths explaining the participation of children below the age of discernment in mosques. These hadiths indicate that the presence of such children in mosques did not disrupt the Prophet (PBUH) in leading prayers, particularly when he served as the imam. . Moreover, the practice of bringing small children, including those under the age of tamyiz, to mosques was common during the time of the Prophet (PBUH) and his companions. Authentic hadiths also show that young children passing in front of those praying were tolerated by the Prophet (PBUH), as there are the mosque has been a child-friendly place ever since the time of the Prophet.[Penelitian ini mengkaji hadis-hadis tentang keikutsertaan anak yang belum tamyiz ke masjid dan bagaimana hadis menyikapi mereka ketika bermain di dalam masjid. Penelitian ini berangkat dari adanya pro dan kontra di tengah masyarakat mengenai keikutsertaan anak-anak yang belum tamyiz ke masjid. Kehadiran mereka kerap dianggap berpotensi menimbulkan kegaduhan serta mengganggu kekhusyukan jamaah, misalnya dengan berjalan di depan orang yang sedang salat. Penelitian ini merupakan penelitian kualitatif dengan metode studi hadis tematik yang dijalankan dengan mengumpulkan, menganalisis, dan menginterpretasikan hadis-hadis yang berkaitan dengan tema yang dibahas. Hasilnya, terdapat banyak hadis sahih yang menjelaskan tentang keikutsertaan anak-anak yang belum tamyiz ke masjid. Hadis-hadis ini menunjukkan bahwa keberadaan anak-anak yang belum tamyiz di masjid tidak mengganggu Nabi SAW dalam melaksanakan salat, terutama ketika beliau menjadi imam. Hadis-hadis ini juga menunjukkan bahwa kebiasaan membawa anak-anak kecil ke masjid, termasuk anak-anak yang belum tamyiz, sudah terjadi di masa Nabi Muhammad SAW dan para sahabat. Hadis-hadis sahih yang menyebutkan keikutsertaan anak-anak yang belum tamyiz ke masjid itu menunjukkan bahwa masjid merupakan tempat ramah bagi anak bahkan sejak zaman Rasulullah.]